Effects of elasticity distribution on pressure and breast displacement for sports bras based on numerical simulation - Xiaofang Liu; Yue Sun; Xiaofen Ji; Kit-lun Yick; Liling Cai (Journal of Engineered Fibers and Fabrics, 2025)
Sports bras knitted with high-Young’s modulus materials are effective in reducing the range of breast movement (ROM), but also increase the contact pressure to the body, leading to discomfort or even body injury. Elasticity distribution was found to be a factor influencing both pressure and ROM, however, the mechanism has yet to be studied, limiting its application in the sports bra industry. This study aimed to investigate the quantitative relationships between Young’s modulus of different parts (C, S f , S b , B, U) and the performance metrics of sports bras in pressure and ROM for the optimization of both performance. A finite element (FE) model was developed to simulate the dynamic peak pressure at four test points and ROM for sports bras with different elasticity distributions during exercise. Based on which, a regression model was formed and the sensitivity factors (φ) were ranked through 2 5 full factorial analysis. The results revealed that the influence of Young’s modulus of each part varied with the pressure test points and the directions of ROM. Notably, the effect on pressure varied based on the placement of the test point relative to the part of sports bra. P 1 , P 2 , and P 4 were greatly influenced by Young’s modulus of the part covering the test point and the parts nearby, whereas P 3 was mainly influenced by U. The effect on ROM predominantly depended on S f , C, and U rather than S b and B. Therefore, the elasticity distribution design with relatively low S b and B, relatively high S f and U, and appropriate C was recommended to optimize both performances. These findings provide novel information for optimizing pressure comfort and breast support performance of sports bras, which is hoped to sever as a valuable reference for sports bra industry.